Pulmonary nocardiosis following COVID-19 in a patient with idiopathic pulmonary fibrosis and lung transplantation: a case report - Cao, Liming; Sun, Yilan; Chen, Fei (Frontiers in Medicine, 2023)
Nocardiosis is an opportunistic infection that primarily affects immunocompromised patients. Pulmonary nocardiosis is the most prevalent form, but can also spread to other organs.Potential causes contributing to opportunistic infection may include immunosuppression and disruption of tight junctions, both of which can result from COVID-19.We reported a case of a 68-year-old male patient who presented with a 10-day history of fever, cough, and productive sputum. Upon physical examination, velcro rales were detected in the right lung, while breath sounds in the left lung were clear. The patient had previously undergone left lung transplantation due to idiopathic pulmonary fibrosis four years ago. He was initially hospitalized and treated for COVID-19 but was readmitted due to worsening symptoms. Subsequently, pulmonary nocardiosis was diagnosed utilizing metagenomic next-generation sequencing of bronchoalveolar lavage fluid. The above-mentioned condition was improved following treatment with cancidas and linezolid. Now, he is under regular follow-up.Conclusions: This case highlights the complexity of COVID-19 and the occurrence of secondary opportunistic infections, which require further investigation.